Does Clinical and Laboratory Markers are Predictive of Radiological Joint Damage in Rheumatoid Arthritis? (Bangladesh Journal of Medicine, 2015)
Aims and objectives. To identify the association of following variables with radiographic findings in rheumatoid arthritis cases in Bangladesh: Age at onset, Duration of suffering, Sex, Clinical indexes of disease activity & Rheumatoid factorMethods. In this observational study, 100 consecutive rheumatoid arthritis patients who met ACR criteria 1987 were enrolled from rheumatology OPD of BSMMU from the period of August 2009- April 2010. Clinical evaluations and laboratory investigations were done in all cases. Final evaluation was done on 96 patients, because 4 patients were dropped out, due to inconclusive radiological report. Radiographs of hands and wrists were scored by Van der Heijde modification of Sharp scoring method.Results. Out of 96 patients 73 were female and 23 male with female male ratio of 3.1:1. Age of onset was 41.0±11.0 (mean ± SD) in male and 37.7±12.9 in female. 90 patients had severe RA among them 21 (23.3%) were male and 69 (76.6%) were female. Rose Waaler (RW) test was positive in 68 cases. Bony erosions were observed in 58 cases, out of them 15 (65.2%) were male and 43 (58.9%) female. Bony erosions were observed in 60.3% cases of positive Rose Waaler and 69.8% in patients whose age at onset was < 45 yrs. Hemoglobin level (gm/dl) was 12.2±1.6 in male and 10.9±1.5 in female. Platelet count was 312142±111233 in male and was 379114±115574 in females.Conclusion: Hemoglobin levels were significantly lower among the anemic women than anemic men. Thrombocytosis was also more in women than men. Higher percentage of bony erosions was observed among the cases of positive RW and whose age at onset was < 45 but it was not statistically significant.Bangladesh J Medicine Jan 2015; 26 (1) : 13-17